THE CONCEPT OF A LEGISLATIVE QUALITY ASSURANCE SYSTEM - Rybikova, Ganna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Objective: to propose a definition of the concept of the system of quality assurance of legislation. Research methods: dialectical method of cognition, general scientific and special methods are used in the article. Results: the author studies the concept of a legislative quality assurance system, which allows for a comprehensive approach to the formation of various aspects of the relevant theoretical construct. The author proposes a comprehensive methodological apparatus for creating a system of ensuring the quality of legislation. It is concluded that the rulemaking process is quite complex, as well as the system of legislation as a whole, and all other systems of the State depend on its quality, and therefore it is necessary to develop such a system for Ukraine. The author also offers her own definition of the concept of "legislative quality assurance system". Discussion: analyzed the need for a legislative quality assurance system in Ukraine to eliminate inefficiency, abuse and opportunities for corruption in public administration, as well as the general scheme with internal and external links between the elements of the system. Any activity requires control and assurance of its quality as a necessary principle of management, in most areas important for humanity such systems are developed (quality assurance of education, food products, medical services, scientific research, etc.). The process of standard-setting is rather complicated, as well as the system of legislation in general, all other systems of the state depend on their quality, so we consider it necessary to eliminate the gap in this sphere and to develop such system for Ukraine. The Ukrainian legislation contains multiple elements of ensuring the quality of legislation. Among the most prominent of them are constitutional procedure for submission, consideration, adoption of draft laws, amendments thereto, accompanied by legal and scientific expertise by the parliamentary apparatus, the procedure for appealing against normative legal acts, etc. The need to study the legislative quality assurance system is due not only internal but also external factors, crucial among which belongs to the development of interstate integration processes, the European vector of development of Ukraine, which requires a clear understanding of the criteria and approaches to ensure the quality of legal acts in the EU as a result of dialogue between different cultural and legal traditions, overcoming the isolation of other legal cultures.